Who gets more out of sport? The role of value and perceived ability in flow and identity-related experiences in adolescent sport. Issue 4 (1st October 2016) - Drane, Catherine F.; Barber, Bonnie L.
ABSTRACT: Sport is a context that provides positive developmental benefits to adolescents. However, these benefits are not distributed equally to all participants. This study examined whether the motivational constructs of attainment value and ability self-concept were related to positive developmental experiences in sport, and tested intensity of participation as a moderator of this relation. A sample of 1, 628 students (954 grade 9, 674 grade 12) reported their developmental experiences in sport in two domains: identity formation and flow. Higher levels of attainment value and ability self-concept in sport were related to more identity and flow experiences. In addition, intensity of participation moderated the links between attainment value and identity and flow, and ability self-concept and identity, for older students. Placing higher value on sport was most strongly related to older students' positive experiences at higher levels of involvement. This study contributes to understanding the role of individual differences in developmental experiences in sport.